A Compact CPW‐Fed Wide‐Slot Ultrawideband Antenna with Sharp Frequency Rejection Functions for Wlan Band and X‐Band. Issue 12 (23rd September 2013) - Li, Yingsong; Li, Wenxing; Yu, Wenhua
ABSTRACT In this article, a coplanar waveguide (CPW)‐fed ultrawideband (UWB) antenna with two sharp frequency rejection functions is proposed. The dual band‐notched characteristic is realized by etching a stepped impedance split‐ring resonator (SISRR) and a stepped impedance resonator (SIR) in a circular radiating patch and a CPW transmission stripline, respectively. The central frequency of the two notch bands can be controlled by adjusting the SISRR and the SIR parameters. Simulation and experimental results obtained for this antenna show that it exhibits a good radiation behavior within the UWB frequency range and it also has the dual band‐notched characteristics in the wireless local‐area networks band and X‐band, which can mitigate the potential interference between UWB systems and the designated existing narrow‐band systems. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2972–2976, 2013